Asuhan Keperawatan Jiwa Pada Nn.R Dengan Masalah Utama Gangguan Konsep Diri: Harga Diri Rendah Di Ruang Dewaruci RSJD dr.Amino Gondohutomo Provinsi Jawa Tengah - Novi Amalia; Slamet Wijaya B; Tati Karyawati (Jurnal Mahasiswa Ilmu Kesehatan, 2023)
According to Maramis (2008), health is one of the most valuable things in life, as is mental health, which is still a significant problem in the world, including in Indonesia. Mental health is a condition where an individual can develop physically, mentally, spiritually and socially so that the individual is aware of his own abilities, can overcome pressure, can work productively and is able to contribute to his community (Febrianto et al., 2019). Mental health is a dynamic condition ranging from mental health to mental disorders. The types of mental disorders that can be found in society are mild mental disorders, for example emotional mental disorders and severe mental disorders, one of which is schizophrenia (Ramadhani et al., 2021).